Modulation of Cellular Cholesterol Transport and Homeostasis by Rab11 - Hölttä-Vuori, Maarit (The American Society for Cell Biology, 2002)
To analyze the contribution of vesicular trafficking pathways in cellular cholesterol transport we examined the effects of selected endosomal Rab proteins on cholesterol distribution by filipin staining. Transient overexpression of Rab11 resulted in prominent accumulation of free cholesterol in Rab11-positive organelles that sequestered transferrin receptors and internalized transferrin. Sphingolipids were selectively redistributed as pyrene-sphingomyelin and sulfatide cosequestered with Rab11-positive endosomes, whereas globotriaosyl ceramide and GM2 ganglioside did not. Rab11 overexpression did not perturb the transport of 1,1′-dioctadecyl-3,3,3′,3′-tetramethyl-indocarbocyanine-perchlorate–labeled low-density lipoprotein (LDL) to late endosomes or the Niemann-Pick type C1 (NPC1)-induced late endosomal cholesterol clearance in NPC patient cells. However, Rab11 overexpression inhibited cellular cholesterol esterification in an LDL-independent manner. This effect could be overcome by introducing cholesterol to the plasma membrane by using cyclodextrin as a carrier. These results suggest that in Rab11-overexpressing cells, deposition of cholesterol in recycling endosomes results in its impaired esterification, presumably due to defective recycling of cholesterol to the plasma membrane. The findings point to the importance of the recycling endosomes in regulating cholesterol and sphingolipid trafficking and cellular cholesterol homeostasis.